Ion beam modification of chitosan and cellulose membranes for simulation of ion bombardment of plant cell envelope - K. Prakrajang (2018)
Ion beam biotechnology has been developed for induction of DNA transfer into biological cells. To separately investigate effects of ion interaction with plant cell envelope for understanding relevant mechanisms, this study used chitosan and cellulose membranes to simulate the cell envelope and characterize behavior of the membranes modified by ion beam. Chitosan and cellulose membranes were bombarded with argon and nitrogen ion beams at energy of 15-25 keV to fluencies in orders of 1015ion/cm2. Modifications of the membrane surface morphology, contact angle and electric characteristics were investigated. Results showed that subjected to ion bombardment, the membrane surface was roughened, the contact angle of the membrane surface was varied, the membrane impedance was decreased and the conductance and capacitance were increased. These modifications explain effects of ion bombardment of plant cell envelope on induction of DNA transfer. © 2009 Elsevier B.V. All rights reserved.